Significados Atribuidos A Los Límites, Jerarquía Y Comunicación Por Parte De Madres E Hijas Pertenencientes A Familias Monoparentales Con Antecedentes Judiciales (2019)
This project involved a population of four women, two single mothers with a judicial background and two of their daughters, who sought to determine the meanings attributed to the boundaries, hierarchy and communication in which they operate as a single parent family. The population accepted the participation, so there were four unstructured interviews that were literally transcribed and a presentation and analysis of results was made, in which the links with their childhood, being mothers and the limits and hierarchies were observed.